1996
DOI: 10.1080/07481189608252747
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among death anxiety, communication apprehension with the dying, and empathy in those seeking occupations as nurses and physicians

Abstract: In light of the modern phenomenon of increased institutionalized deaths occurring in hospitals and in nursing homes, much of recent death attitude research has focused on health professionals. The present study explored possible relationships among measures of death anxiety, communication apprehension with the dying, and empathy in undergraduate nursing, premedical, and control subjects. Main effects for year in school indicated that seniors scored lower than freshmen on communication apprehension with the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 28 publications
1
25
1
Order By: Relevance
“…Early death anxiety studies from college students found that they were more likely to fear the dying and death of others over the dying and death of self. [22][23][24][25][26][27][28] Students cognitively acknowledged that death was a natural part of living but most of them did not like the idea of death. Our students conceded the nature of the relationship with the patient and the family can cause increased emotionality.…”
Section: Discussionmentioning
confidence: 97%
“…Early death anxiety studies from college students found that they were more likely to fear the dying and death of others over the dying and death of self. [22][23][24][25][26][27][28] Students cognitively acknowledged that death was a natural part of living but most of them did not like the idea of death. Our students conceded the nature of the relationship with the patient and the family can cause increased emotionality.…”
Section: Discussionmentioning
confidence: 97%
“…101-508) to inquire of all adult patients whether they possess advance directives or would like to execute one. Although research suggests that death attitudes do influence the behavior of health care professionals (Haisfield-Wolfe, 1996;Kaye, Gracely, & Loscalzo, 1994;Servaty, Krejci, & Hayslip, 1996), no extant research has explored the influence of personal death attitudes and experiences on practitioners' advance directive communication behavior.…”
mentioning
confidence: 98%
“…Lastly, a study comparing nursing and pre-med students found no significant differences between disciplines relative to levels of communication apprehension with the dying. However, a significant, positive correlation between death anxiety and communication apprehension among groups was detected (r ¼ .42, p < .01; Servaty et al, 1996).…”
Section: Nursing and Medicine And End-of-life Carementioning
confidence: 89%
“…A general review of health-care professionals and comfort with end-of-life issues found studies conducted with nursing students and nurses (Allchin, 2006;Beck, 1997;Deffner & Bell, 2005;Demmer, 2000;Lewis, Espe-Pfeifer, & Blair, 1999;Payne, Dean, & Kalus, 1998;Servaty, Krejci, & Hayslip, 1996), as well as medical students and physicians (Kvale, Berg, Groff, & Lange, 1999;Lloyd-Williams & Dogra, 2003;Servaty et al, 1996;Williams, Wilson, & Olsen, 2005). In one qualitative study (Allchin), interviews with nursing students revealed care themes that included an initial hesitancy and discomfort in end-of-life situations, a need for emotionally processing the experience of providing care to the dying, and an eventual sense of personal and professional benefit from this work.…”
Section: Nursing and Medicine And End-of-life Carementioning
confidence: 99%
See 1 more Smart Citation